Scalable synthesis of silacyclohexanones and ready access to silicon building blocks - Ramesh, Eagala; Nandawadekar, Laxman D.; Rao, Ramana Sreenivasa; Reddy, D. Srinivasa (Organic Letters, 2023)
A simple and efficient two-step method for the synthesis of silacyclohexanones starting from bis(bromoethylsilanes) using TosMIC is presented. The prepared silacyclohexanones were transformed to nine different heterocycles with silicon incorporation. In addition, the developed methodology was used for the synthesis of a sila analogue of the HDAC6 inhibitor tubastatin A.